Faktor-faktor yang mempengaruhi perilaku merokok di kalangan remaja - Desmon Wirawati; Sudrajat Sudrajat (Holistik Jurnal Kesehatan, 2021)
Factors influencing smoking behavior among adolescentsBackground:  Base on research that the overall smoking prevalence among Indonesian adolescents is 7.2%. The prevalence is substantially higher among males compared to females. Smoking behavior started with curiosity and peer influence and also occurs because of the influence of the social environment.Purpose : To know the factors influencing smoking behavior among adolescentsMethod: A quantitative approach, the population is teenagers as student status at government Junior High School Kelapa Dua, Tangerang Banten and the sample is 659 respondents using a total sampling technique. The questionnaire had tested for validity and reliability before being used.The instrument used to measure the level of knowledge is a knowledge questionnaire using a true and false linker scale and analyzed using the chi-square test.Results:  The finding that adolescents' knowledge was in a good category 59.51% regarding of health effects of cigarette smoking. The biggest risk factor for adolescents to smoke is family members who smoke at the home of 69.33%.Conclusion : Knowledge among adolescents about the impact of smoking on health is still relatively good but has a smoking risk factor, namely the presence of family members who smoke. The recommendation for the management of the public health center, keep always promote the impact of smoking on health in every family towards a physically and mentally healthy family.Keywords: Influencing; Smoking; AdolescentsPendahuluan: Prevalensi merokok secara keseluruhan di kalangan remaja Indonesia adalah 7,2%, Prevalensi secara substansial lebih tinggi di antara laki-laki dibandingkan dengan perempuan. Perilaku  merokok  diawali oleh rasa ingin tahu dan pengaruh teman sebaya. Remaja mulai merokok terjadi akibat pengaruh lingkungan sosial.Tujuan: Mengetahui Faktor-faktor yang mempengaruhi perilaku merokok di kalangan remajaMetode: Pendekatan kuantitatif, populasinya adalah remaja berstatus pelajar SMP Negeri Kelapa Dua Tangerang Banten dan sampel sebanyak 659 responden dengan teknik total sampling. Kuesioner telah diuji validitas dan reliabilitasnya sebelum digunakan. Instrumen yang digunakan untuk mengukur tingkat pengetahuan adalah angket pengetahuan menggunakan skala linker benar dan salah dan dianalisis menggunakan uji chi-square.Hasil: Pengetahuan remaja dalam kategori baik 59,51% tentang dampak merokok terhadap kesehatan. Faktor risiko terbesar remaja untuk merokok adalah anggota keluarga yang merokok di rumah sebesar 69,33%.Simpulan: Pengetahuan di kalangan remaja tentang dampak rokok bagi kesehatan masih tergolong baik namun memiliki faktor risiko merokok yaitu adanya anggota keluarga yang merokok. Saran bagi pengelola Puskesmas, tetap selalu mensosialisasikan dampak rokok terhadap kesehatan pada setiap keluarga menuju keluarga yang sehat jasmani dan rohani.